A novel modified penile disassembly procedure for isolated male epispadias repair: preliminary outcomes - Deng, Fuming; Fu, Wen; Liu, Guochang; Sun, Liangzhong (Frontiers in Pediatrics, 2024)
The aim of this study was to evaluate the preliminary outcome of a novel modification of a penile disassembly procedure.We retrospectively reviewed the data of 15 patients with isolated male epispadias (IME) who underwent a modified penile disassembly procedure. The modification was characterized by leaving the glans connected while the urethral plate was dissected from the corpus cavernosum. Such a modification reserves the bundles of the anastomosis at the glans, which can prevent ischemic changes.Results: One of the first two patients experienced glans ischemic changes on the first day after the operation, which ultimately resulted in the loss of half of the hemiglans. Urethral plate shortening was found in two patients and was addressed with a transverse preputial island flap. Two patients had a penopubic urethral fistula that was repaired six months postoperatively. We found that 10 of the 15 patients (66%) were continence or social continence, and four patients were incontinent and needed bladder neck reconstruction. One patient had not yet reached the age for continence evaluation. Two patients had a residual dorsal curvature of approximately 10-15 degrees and were advised to undergo continuous follow-up.The modified penile disassembly procedure is a simple, effective and safe method for IME repair with an acceptable penile appearance and complication rate.